Removal of Sulfur from CaF2 Containing Desulfurization Slag Exhausted from Secondary Steelmaking Process by Oxidation - Hiraki, Takehito; Kobayashi, Junichi; Urushibata, Satomi; Matsubae, Kazuyo; Nagasaka, Tetsuya (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2012)
The oxidation behavior of sulfur in desulfurization slag generated from the secondary steelmaking process with air has been investigated in the temperature range of 973 K to 1373 K (700 °C to 1100 °C). Although a high removal rate of sulfur is not achieved at temperatures lower than 1273 K (1000 °C) because of the formation of CaSO 4 , most of the sulfur is rapidly removed from slag as SO 2 gas in the 1273 K to 1373 K (700 °C to 1100 °C) range. This finding indicates that the desulfurization slag generated from the secondary steelmaking process can be reused as a desulfurized flux through air oxidation, making it possible to reduce significantly the amount of desulfurization slag for disposal.